Updated keys to the genera in the subfamilies of Cyclocoelidae Stossich, 1902, including a reconsideration of species assignments, species keys and the proposal of a new genus in Szidatitreminae Dronen, 2007 - Dronen, Norman O.; Blend, Charles K. (Zootaxa, 2015)
Keys to the six subfamilies, 22 genera within subfamilies and 128 species recognized within the Cyclocoelidae are provided. Lists of species in each genus are provided, along with taxonomic summaries that include type host, type locality, additional hosts, additional localities, previously proposed synonyms, and remarks for each species. The following synonymies are proposed: Cyclocoelum mutabile (Zeder, 1800)—Syn. C. microstomum (Creplin, 1929); Cyclocoelum leidyi Harrah, 1922—Syn. C. cuneatum Harrah, 1922; Cyclocoelum mehrotrai Sinha & Sahay, 1975—Syn. C. mathuri Jain, 1984; Selfcoelum allahabadi (Khan, 1935) n. comb.—Syns. Cyclocoelum agamprasadi Jain, 1983, Cyclocoelum erythropis Khan, 1935 and Cyclocoelum indicum Khan, 1935; Selfcoelum obliquum (Harrah, 1921) n. comb.—Syn. Cyclocoelum mehrii Khan, 1935; Uvitellina adelphus (Johnston, 1917)—Syn. Cyclocoelum (Uvitellina) dollfusi Tseng, 1930; Uvitellina kaniharensis (Gupta, 1958)—Syn. U. indica Siddiqi & Jairajpuri, 1962; Uvitellina simile (Stossich, 1902) n. comb.—Syn. U. magniembria Witenberg, 1923; Uvitellina vanelli (Rudolphi, 1819)—Syns. U. keri Yamaguti, 1933 and U. tageri Yamaguti, 1933; Wardianum triangulare (Harrah, 1922)—Syn. Wardianum catoptrophori Dronen, 2007; Haematotrephus limnodromi Dronen, Gardner & Jiménez, 2006—Syn. H. selfi Dronen, Gardner & Jiménez, 2008; and Hyptiasmus arcuatus (Brandes, 1892 of Stossich, 1902)—Syn. H. coelonodus Witenberg, 1923. Based on the lack of adequate descriptive information, Cyclocoelum cornu (Zeder, 1800); Cyclocoelum crenulatum (Rudolphi, 1809); Haematotrephus nigropunctatum (von Linstow, 1883) n. comb.; Haematotrephus robustus Ukoli, 1968; Hyptiasmus californicus (Wootton, 1966); and Hyptiasmus vigisi Savinov, 1960 are considered to be species inquirendae. Hyptiasmus witenbergi Tret’iakova, 1940 (described in a dissertation) is considered to be a nomen nudum. Comparative tables containing measurements, morphometric percentages and morphometric ratios for species in the family are provided and the comparative characteristics used to distinguish species in the Cyclocoelidae are discussed.